2020
DOI: 10.1016/j.molmet.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

NPY1R-targeted peptide-mediated delivery of a dual PPARα/γ agonist to adipocytes enhances adipogenesis and prevents diabetes progression

Abstract: ObjectivePPARα/γ dual agonists have been in clinical development for the treatment of metabolic diseases including type 2 diabetes and dyslipidemia. However, severe adverse side effects led to complications in clinical trials. As most of the beneficial effects rely on the compound activity in adipocytes, the selective targeting of this cell type is a cutting-edge strategy to develop safe anti-diabetic drugs. The goal of this study was to strengthen the adipocyte-specific uptake of the PPARα/γ agonist tesaglita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 121 publications
0
13
0
Order By: Relevance
“…These dual agonists improve lipid parameters and reduce cardiovascular complications through PPARα in addition to the insulin-sensitizing effects mediated via PPARγ [156]. Combined with a cutting-edge approach for cell-type specific uptake of PPARα/γ dual agonists by peptide-mediated internalization and controlled release into adipocytes, these compounds could potentially reduce the intolerable side effects of PPARγ agonists and provide major benefit for the treatment of DM2 [157].…”
Section: Therapeutic Exploitation Of Pparsmentioning
confidence: 99%
“…These dual agonists improve lipid parameters and reduce cardiovascular complications through PPARα in addition to the insulin-sensitizing effects mediated via PPARγ [156]. Combined with a cutting-edge approach for cell-type specific uptake of PPARα/γ dual agonists by peptide-mediated internalization and controlled release into adipocytes, these compounds could potentially reduce the intolerable side effects of PPARγ agonists and provide major benefit for the treatment of DM2 [157].…”
Section: Therapeutic Exploitation Of Pparsmentioning
confidence: 99%
“…It has received great pharmaceutical potential when the group of Reubi reported specific overexpression of the Y 1 R in breast cancer and derived metastases [27] . Moreover, the receptor has been targeted with toxophore‐loaded peptides [18] or boron‐containing peptides for boron‐neutron‐capture therapy, [17] which requires high amounts of boron delivered. Previous investigations have already characterized that the Y 1 R internalizes after ligand stimulation in an arrestin‐dependent mechanism and specific binding motifs for arrestin have been identified [21,28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Wittrisch et al. reported high levels of hY 1 R in human adipose tissue, 3T3‐L1 preadipocytes as well as adipocytes [18] . Hence, the Y 1 R is of great pharmaceutical interest and displays an attractive and promising drug shuttle target for both, cancer and obesity [15] …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that ITGB4 [143], SEMA3D [144], FCAR (Fc fragment of IgA receptor) [145], KIT (KIT proto-oncogene, receptor tyrosine kinase) [146], PGLYRP1 [147], IL17RB [148], BIRC5 [149] and PTGS1 [150] plays an important role in asthma, but these genes might be linked with progression of obesity associated type 2 diabetes mellitus. GRK2 [151], ADCY3 [152], FASN (fatty acid synthase) [153], DGKD (diacylglycerol kinase delta) [154], DGKQ (diacylglycerol kinase theta) [154], IP6K1 [155], ANXA1 [156], SUCNR1 [157], PRNP (prion protein) [158], CXCR4 [159], CAV1 [160], LCN2 [161], AQP9 [162], NMU (neuromedin U) [163], NPY1R [164], FFAR2 [165], OSM (oncostatin M) [166] and TREM1 [167] were reported in obesity associated type 2 diabetes mellitus. UNC13B [168], PFKFB3 [169], FCN1 [170] and SLC11A1 [171] were involved in progression of type 1 diabetes, but these genes might be liable for progression of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%